Ethnicity and Migrations in the Late Antique and Early Medieval Middle Danube Basin. Examples Linking Modern Croatian and Slovakian Areas - Gračanin, Hrvoje (2011)
The proposed paper endavours to survey and analyze the ethnic changes in the middle Danube basin during Late Antiquity and early Middle Ages (late 4th-late 9th centuries), with particular regard to the territories of modern Croatia and Slovakia. The main emphasis will be directed towards comparative study of the impact of migratory and ethnogenetic processes in respective areas. Specifically, the study will be centered around more or less distinct periods: 1) movements of various ethnic groups in late 4th and early 5th centuries ; 2) time of Hunnic domination ; 3) period of Germanic „states“ in the Carpathian basin ; 4) arrival of the Avars and establishment of the Slavic populations ; 5) situation under Avar domination ; 6) the creation of new political realities in the 9th century. The intention is also to determine and explain the differences and similarities in historical patterns in given chronological frame relevant for both areas.
Projekt MZOS
Projekt MZOS
ENG